205 Is it a brain tumour? Assessment on performance of the CNS two week wait pathway. Issue 6 (27th May 2022) - Shanmugalingam, Thurkaa; Quattrocchi, Graziella
Abstract : Background: In June 2015, NICE published updated two week wait (2WW) referral guidelines for general practitioners (GPs) for patients with suspected central nervous system (CNS) tumours. These include guidance on relevant clinical information and recommendations for using brain imaging. We reviewed all cases referred to Lewisham and Greenwich (L&G) NHS Trust sites (University Hospital Lewisham (UHL) and Queen Elizabeth Hospital (QEH)) through this pathway with the aim of identifying the appropriate- ness of referrals and reflect on ways to improve this pathway. Methods and Results : A total of 233 cases were referred onto the 2WW pathway for suspected CNS cancer across L&G NHS Trust between April and October 201; of which 62 were referred to UHL and 161 to QEH. Electronic records and clinic letters were reviewed. Demographics, reason of referrals, target times, and clinical outcome were recorded. 97.7% of these referrals were seen within the target wait of two weeks. Headache was the most common cause for referral. Discussion: The annual GPs consultation for headache is 4.4 per 100 patients, of which 2% are referred to secondary care. Compliance may be improved by implementing educational programmes in the primary care setting or redesigning the form to optimise referrals. thurkaa.shanmugalingam@doctors.org.uk